Improving the properties of coconut milk-based functional drink with lactic acid bacteria fermentation and addition of herbal leaf - Muspirah Djalal; Dinda Amalia; Adila Oktavia; Mulyati M Tahir; Arfina Sukmawati Arifin; Serli Hatul Hidayat; Prakoso Adi; Nurul Wakiah (jurnal1, 2025)
Coconut milk possesses potential as promising plant-based milk, alternative to animal milk. With the incorporation of bioactive-rich herbal leaves in combination with fermentation, the coconut milk presents an opportunity for better functional attributes, particularly antioxidant and antibacterial activities. This research investigates the effects of fermentation (lactic acid bacteria (culture)-mediated and spontaneous) and the addition of herbal leaves (cassava, bay, and guava) on the physicochemical and biofunctional properties of coconut milk drinks. Besides analysing antioxidant and antibacterial activities, other parameters analysed in this study include pH, total acidity, soluble solids (°Brix), total dissolved solids (ppm), and viscosity. This study finds that fermentation significantly reduced pH and the soluble solids (°Brix) while increasing total acidity, viscosity, and dissolved solids (ppm). It was also found that both fermentation and the addition of herbal leaves had significant effect on the biofunctional properties of the coconut milk drink in which they are found to enhance the antioxidant activity, with guava leaves exhibiting the highest enhancement. Particularly in guava-enriched formulations, the antibacterial properties were found to increase after fermentation demonstrating notable efficacy against E. coli (up to 7.03 mm) and S. aureus (up to 8.37 mm). This finding underscores the potential of fermentation in combination with herbal leaves to enhance the potential of plant-based milk.